(untitled) (Research, Society and Development, 2025)
Objective: To synthesize evidence on nursing interventions and routines for preventing and managing oral mucositis in people undergoing cancer treatment, highlighting implications for clinical practice and the community. Methods: Integrative review conducted in accordance with PRISMA. Searches were performed in MEDLINE/PubMed, Embase, CINAHL, LILACS, and SciELO using DeCS/MeSH descriptors and free terms; two reviewers independently selected studies, carried out standardized data extraction, and appraised methodological quality (JBI/CASP). Narrative synthesis was organized by thematic axes. Results: Structured oral-hygiene protocols (soft toothbrush, saline/bicarbonate solutions), serial assessment with validated scales, cryotherapy for specific chemotherapy regimens, and photobiomodulation/low-level laser therapy were associated with reduced incidence and severity of mucositis and with pain relief. Additional components included health education for patients and families, prevention of opportunistic infections, and multimodal pharmacologic management. Heterogeneous protocols and short follow-up periods limited comparability and generalizability. Conclusion: Nurses play a central role in preventing and caring for oral mucositis by integrating assessment, health education, and care coordination, positively affecting treatment adherence and quality of life. Institutional protocols, team training, serial oral assessment, and access to safe technologies such as cryotherapy and photobiomodulation are recommended, alongside robust studies across different levels of care.